2022
DOI: 10.1007/s11440-022-01618-1
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional particle finite element model for simulating soil flow with elastoplasticity

Abstract: Soil flow is involved in many earth surface processes such as debris flows and landslides. It is a very challenging task to model this large deformational phenomenon because of the extreme change in material configurations and properties when soil flows. Most of the existing models require a two-dimensional (2D) simplification of actual systems, which are however three-dimensional (3D). To overcome this issue, we develop a novel 3D particle finite element method (PFEM) for direct simulation of complex soil flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…In the last decades, many different numerical models for the simulation of debris flows and flow-like landslides have been developed. Due to the simpler governing equations and less computational time compared with the fully 3D numerical models, such as the 3D models based on smoothed particle hydrodynamics (SPH) (Wang et al, 2016;Dai et al, 2017), material point method (MPM) (Li et al, 2020;Vicari et al, 2022) and particle finite element method (PFEM) (Zhang et al, 2020;Wang and Zhang, 2022), depth-averaged models derived from the principles of continuum mechanics have been widely applied to reproduce and analyze the dynamic processes of flow-like landslides. The unsteady debris flow model for simulating erosion/deposition process of sediment during the flow was proposed (Chen, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, many different numerical models for the simulation of debris flows and flow-like landslides have been developed. Due to the simpler governing equations and less computational time compared with the fully 3D numerical models, such as the 3D models based on smoothed particle hydrodynamics (SPH) (Wang et al, 2016;Dai et al, 2017), material point method (MPM) (Li et al, 2020;Vicari et al, 2022) and particle finite element method (PFEM) (Zhang et al, 2020;Wang and Zhang, 2022), depth-averaged models derived from the principles of continuum mechanics have been widely applied to reproduce and analyze the dynamic processes of flow-like landslides. The unsteady debris flow model for simulating erosion/deposition process of sediment during the flow was proposed (Chen, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, solutions to the saturated soils problems 8 and the partially saturated soils problems, 9 seismic failure of layered clayey slopes, 10 offshore geotechnical engineering problems, 11 and 3D soil flow problems. 12 A state-of-the-art review of the PFEM can be found in Cremonesi et al 13 The PFEM is actually an updated-Lagrangian approach with nodes treated as particles.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the PFEM has been very successfully applied to geomechanics problems. In particular, solutions to the saturated soils problems 8 and the partially saturated soils problems, 9 seismic failure of layered clayey slopes, 10 offshore geotechnical engineering problems, 11 and 3D soil flow problems 12 . A state‐of‐the‐art review of the PFEM can be found in Cremonesi et al 13 .…”
Section: Introductionmentioning
confidence: 99%